Wood handbook : wood as an engineering material. (General technical report FPL, 1999)
This handbook is intended as an aid to more efficient use of wood as a construction material. It provides engineers, architects, and others with a source of information on the physical and mechanical properties of wood and how these properties are affected by variations in wood.